Some Reflexions on the Study of Idioms and Consequences for L2 Teaching - Marisa Díez Arroyo (Miscelánea: A Journal of English and American Studies, 2000)
This paper focuses on the importance of a particular manifestation of figurative language: the idiomatic phrase. Its purpose is to analyse fixed expressions, the difficulties they pose and the main preoccupations shown by theoreticians. At the same time, the study offers a comparison of idioms in L1 with the circumstances which surround L2 learning, together with an exploration of how the emerging differences affect L2 idiom teaching. The investigation has been conducted along the lines of an interdisciplinary methodology; thus, a conscious effort has been made to combine the linguistic and the psycholinguistic viewpoints, implemented with the analysis of Proficiency level coursebooks, in the hope that this helps us to gain a better understanding of the mature, processing and teachability/learnability of these phrases.